Reducing speed and sight: how adaptive is post-error slowing? - Ullsperger, Markus; Danielmeier, Claudia (Elsevier, 2016)
After errors, humans and monkeys dynamically change decision boundaries which results in posterror slowing of decisions. Simultaneously decreased sensitivity to sensory information counteracts post-error increases in accuracy. Early post-error adjustments thus reflect rather a general orienting reflex than goal-directed adaptation.